Implantation outcome is Associated with Mucin-16, MiR- 1226 and MiR-210 Expression during IVF of Iraqi Females - Israa M.Majeed; M. Salih Almohaidi, Asmaa (Iraqi Journal of Pharmaceutical Sciences, 2025)
One of the main obstacles to early pregnancy and assisted reproduction is embryo implantation failure. Endometrial receptivity and the interactions between the embryo and the mother determine implantation. The control of implantation involves several molecules. One such molecule is microRNA (miRNA), which is known to have a role in embryo implantation as a transcriptional regulator of gene expression. The current study evaluates the Expression level of miR-210 and miR-1226 with mucin-16 in infertile females under the IVF program and its influence on embryo implantation by measuring the fold change. This study included 26 successful implantations and 58 failed implantations under an in vitro fertilization program and 44 fertile females as control divided into two subgroups, 21 successful implantations and 23 failed implantations. The first conclusion in the current work is that the infertility cases under the IVF program with fertile failure implantation cases related to significant up-regulation of mucin-16, except successful fertile cases, recorded significant down-regulation. There is a significant positive correlation between mucin16 and miR-210-HG in failure embryo implantation in infertile females and a negative correlation between mucin16 with miR-210-HG and miR-1226 in failure embryo implantation in fertile females. These results recorded that up-regulation of miR-210 and miR-1226 gene expression may affect embryo implantation by regulating mucin-16 gene expression in infertile and fertile females undergoing IVF programs.